The effect of postoperative ventilation strategies on postoperative complications and outcomes in patients with esophageal atresia: Results from the Turkish Esophageal Atresia Registry - KIYAN, GÜRSU (My University, 2022)
© 2022 Wiley Periodicals LLC.Objectives: Postoperative ventilatory strategies in patients with esophageal atresia (EA) and tracheoesophageal fistula (TEF) may have an impact on early postoperative complications. Our national Esophageal Atresia Registry was evaluated to define a possible relationship between the type and duration of respiratory support on postoperative complications and outcome. Study Design: Among the data registered by 31 centers between 2015 and 2021, patients with esophago-esophageal anastomosis (EEA)/tracheoesophageal fistula (TEF) were divided into two groups; invasive ventilatory support (IV) and noninvasive ventilatory support and/or oxygen support (NIV-OS). The demographic findings, gestational age, type of atresia, associated anomalies, and genetic malformations were evaluated. We compared the type of repair, gap length, chest tube insertion, follow-up times, tensioned anastomosis, postoperative complications, esophageal dilatations, respiratory problems requiring treatment after the operation, and mortality rates. Results: Among 650 registered patients, 502 patients with EEA/TEF repair included the study. Four hundred and seventy of patients require IV and 32 of them had NIV-OS treatment. The IV group had lower mean birth weights and higher incidence of respiratory problems when compared to NIV-OS group. Also, NIV-OS group had significantly higher incidence of associated anomalies than IV groups. The rates of postoperative complications and mortality were not different between the IV and NIV-OS groups. Conclusion: We demonstrated that patients who required invasive ventilation had a higher incidence of low birth weight and respiratory morbidity. We found no relation between mode of postoperative ventilation and surgical complications. Randomized controlled trials and clinical guidelines are needed to define the best type of ventilation strategy in children with EA/TEF.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SOLUNUM SİSTEMİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; RESPIRATORY SYSTEM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Akciğer ve Solunum Tıbbı; Pediatrics, Perinatology and Child Health; Pulmonary and Respiratory Medicine; complication; esophageal atresia; mechanical ventilation; tracheoesophageal fistula; complication; esophageal atresia; mechanical ventilation; tracheoesophageal fistula